Cloning and expression of cellulosimicrobium cellulans β-1,3-glucanase gene in lactobacillus plantarum to create new silage inoculant for aerobic stability - Bahri Devrim ÖZCAN; Numan ÖZCAN; Makbule BAYLAN; Ali İrfan GÜZEL (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2013)
In this study, the recombinant plasmid pTE353-βG was created by inserting the p353-2 cryptic plasmid region of pLP3537 into pTEG5 recombinant plasmid contains pUC18 and β-1,3-glucanase gene of Cellulosimicrobium cellulans. The recombinant plasmid pTE353-βG was then introduced into Lactobacillus plantarum by electroporation. Insert analysis of pTE353-βG digested with SacI produced 1.9 kbp β-1,3-glucanase gene band on agarose gel as well as 1.9 kbp DNA encoding β-1,3-glucanase gene insert amplified on the recombinant vector via PCR indicated the integration of the gene into the plasmid. Recombinant L. plantarum colonies with pTE353-βG on MRS-laminarin-agar plate showed clear positive zones by Congo-red staining that revealed the expression of β-1,3-glucanase encoding gene. The β-1,3-glucanase enzyme of recombinant strain produced the same activity band with C. cellulans enzyme in terms of molecular weight, which showed the activity of secreted protein without any proteolytic degradation. Optimal temperature and pH values of L. plantarum β-1,3-glucanase have been determined 40ºC and 6.0 respectively, by enzymatic analysis. These results revealed that recombinant L. plantarum could be considered as a silage inoculant for aerobic spoilage of silage.